Developing an SMS gateway-based library information system to enhance efficiency and accessibility - Hidayat, Wahyu; Veza, Okta; Adi, Novi Hendri; Isaev, Ruslan; Erdolatov, Sanzharbek (Researcher and Lecturer Society, 2025)
The integration of technology into library management plays a crucial role in improving operational efficiency and resource accessibility. This study presents the development of an SMS gateway-based library information system to digitalize book borrowing and returning processes. The system was developed using the System Development Life Cycle (SDLC) methodology, incorporating Requirement Planning, System Design, and Implementation phases. The implementation of the system was evaluated by using Black Box Testing to ensure functional correctness. The results indicate that the system effectively streamlines library operations by providing automated notifications for due dates, optimizing inventory tracking, and reducing manual record-keeping errors. Additionally, the integration of an SMS Gateway enhances user engagement and minimizes overdue returns. This study highlights the potential of digital solutions in modernizing library management and serves as a model for other educational institutions aiming to enhance their library systems through technology.